2007
DOI: 10.3354/cr034039
|View full text |Cite
|
Sign up to set email alerts
|

The urban heat island in Salamanca (Spain) and its relationship to meteorological parameters

Abstract: An urban heat island (UHI) was found to exist in Salamanca, Spain -a medium-sized European city that has a continental climate and relatively little industrial pollution. We demonstrate that urban heating can occur in cities with these characteristics, giving rise to a microclimate that may alter the biological rhythm of the zone e.g. under these conditions, spring arrives earlier in the urban zone then in the rural zone. The study was carried out using data from 2 recording stations (one in and the other outs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 16 publications
(18 reference statements)
2
13
0
2
Order By: Relevance
“…Em Lisboa, a IC apresenta uma intensidade média de 2,5ºC, dependendo a sua configuração espacial dos regimes de vento e da situação sinóptica. A intensidade média nocturna -calculada a partir da diferença entre a temperatura da cidade e um ponto nos arredores -é maior do que noutras cidades da Península Ibérica, como Salamanca (1,3ºC) (Alonso et al, 2003) e Granada (2ºC) (Montálvez et al, 2000), e menor do que em Barcelona (2,9ºC) (Moreno, 1994).…”
Section: Discussionunclassified
“…Em Lisboa, a IC apresenta uma intensidade média de 2,5ºC, dependendo a sua configuração espacial dos regimes de vento e da situação sinóptica. A intensidade média nocturna -calculada a partir da diferença entre a temperatura da cidade e um ponto nos arredores -é maior do que noutras cidades da Península Ibérica, como Salamanca (1,3ºC) (Alonso et al, 2003) e Granada (2ºC) (Montálvez et al, 2000), e menor do que em Barcelona (2,9ºC) (Moreno, 1994).…”
Section: Discussionunclassified
“…However, very strong winds prevent the development of the UHII [31]. Winds of about 6 and 7 m/s are critical values for the existence of the maximum UHII in Seoul (South Korea) and Salamanca (Spain) [32,33]. In Lisbon, it was observed that from 8 m/s on, strong intensity urban heath islands do not occur (Figure 10(a)).…”
Section: The Relationship Between Urban Heat Island (Uhi)mentioning
confidence: 99%
“…Mohan et al (2013) also reported that the UHI intensity varies significantly in different parts of Delhi because of different densities of the built-up structures. The external meteorological factors known to modulate the UHI intensity include cloudiness, solar radiation, and wind speed (Unger et al 2001;Morris et al 2001;Fast et al 2005;Souch and Grimmond 2006;Alonso et al 2007;Steeneveld et al 2011). The dependence of UHI intensity on the meteorological factors varies significantly among different times and different locations.…”
Section: Introductionmentioning
confidence: 99%